Avaliação de sistemas de produção de batata orgânica em propriedades familiares: uma aplicação da metodologia multicritério de apoio à decisão (MCDA). - Reichert, Lírio José (2012)
The farm production systems, in general, have a certain degree of complexity because it involves a set of variables that the farmer can not always control, and requires a decision-making. The farmer does it considering his rationality based on his objectives, perception, intuition, and information. Even with all these precautions, it s not always easy to make those decisions, and so they often need some support or some tool to assist them, even more when the production systems involve practices and/or organic production processes or with technological innovation. In these cases, the farmer needs to involve a number of internal and external elements to the rural property, interact with nature and know how to use it for the benefit of the production unit. A number of studies have been conducted to improve organic production processes, emphasizing its importance and its social, environmental and economic benefits, and the opportunities it brings. Potato organic production has evolved, but, being a system still in consolidation, it faces bottlenecks in production and in marketing, which should be studied deeper. Following this idea, the study aimed to construct models that aggregate different systems evaluation criteria of organic potato developed by family farmers from southern Rio Grande do Sul state. The study had the participation of a group that has been in the research project Rede de Referência (GRR) of Embrapa Clima Temperado, and another group out of the network (GFRR), associated with Cooperativas Sul Ecológica, Arpa-Sul and Coopar. To evaluate the organic potato system, the study used the decision aid multicriteria tool, which allows the inclusion of the subjective view of the actors involved in the decision-making context through formation of a mental frame of reference (QRM), composed of their personal beliefs, assumptions, values and preferences, through modeling criteria construction in a participatory manner. The study showed, in general, that the models constructed (1-GRR and 2-GFRR) do not differ much from the production practices adopted in each group. Nevertheless, the differences occurred in the levels of impact of actions, and in the establishment of different weights between the models, so the final result in order of preference of evaluation criteria was different. For GRR the criterion potato size was the most important, whereas for GFRR was the criterion production risks. When evaluated with four other organic potato production systems (A, B, C, and D), the two models performances were very close. In model 1 the scores were 72.6; 70.2; 4.1, and 10.9, and in model 2, 71.7; 71.3; 2.7, and 5.0, respectively. In the assessment of each group, the farmers agreed with the results obtained in the models, proving their validity and robustness against the models constructed.